USING VIDEO YOU TUBE ENVIRONMENT-BASED IN TEACHING ENGLISH TO IMPROVE STUDENTSâ WRITING SKILL - Al Hakim, Luqman (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The article aims at presenting the description of using You Tube environmental based inteaching English to improve studentsâ writing skill. The subject of the research is the 4thsemester students of the English Department Program of Slamet Riyadi University in theacademic year of 2014/2015. The method of the research is a classroom action research. Theresearch was conducted in two cycles. In the 1st cycle, it consists of four meetings in which itincludes pre-test, twice of treatment, and post-test one. Meanwhile, 2nd cycle comprises threemeetings; those are twice of treatment and a post-test two. The sources of the data cover primaryand secondary data. The primary data is informants; those are the students and the writinglecturer. Then, the secondary data is the document, i.e. lesson plan, questionnaire, and soon. Thetechniques of collecting the data are tests, observation, questionnaire, documentation, anddocument. Meanwhile, to analyze the data, the researcher use quantitative and qualitative dataanalysis. The quantitative data analysis is obtained with the comparison of mean score betweenpre-test and post-test one and post-test one and post-test two. Subsequently, the qualitative dataanalysis uses data description, data display, data reduction, and drawing conclusion. The resultof the research shows that there is improvement of the studentsâ achievement after cycle one andcycle two. The mean score of pre-test is 60.63, meanwhile post-test one is 70.37. It means thatthere is improvement after cycle one. Subsequently, the mean score of post-test two is 71.05. Itcan be concluded that there is also improvement of after cycle two, although it is not significant.Based on the research findings, it can be concluded that the achievement of the studentsimproved after cycle one and cycle two in which it is higher than the criterion of minimumachievement, namely 70. It is because they have clear understanding about what they wouldwrite and they have adequate basic writing.Keywords: Writing Skill, You Tube Video, Teaching English